ETIKA PRODUKSI PERSPEKTIF EKONOMI ISLAM - Sukarno, Fahrudin (Al-Infaq: Jurnal Ekonomi Islam, 2010)
This study is aimed to analyse the Islamic production concept rely on its urgence in increasing human welfare in Islam society. The currency problem lied on creating the ethic axioms of production concept based on al-Qur’an and as-Sunnah. The conceptual framework of Islamic production concept is emerging the morality basic in order to implement production activities. This morality basic will affect to economic growth, distributive justice, environmental conservasion program, and also corporate social responsibility.